Microwave Assisted Pretreatment of Szarvasi (Agropyron elongatum) Biomass to Enhance Enzymatic Saccharification and Direct Glucose Production - Jablonowski, Nicolai D.; Pauly, Markus; Dama, Murali (Frontiers in Plant Science, 2022)
Biomass from perennial plants can be considered a carbon-neutral renewable resource. The tall wheatgrass hybrid Szarvasi-1 (Agropyron elongatum, hereafter referred to as “Szarvasi”) belongs to the perennial Poaceae representing a species, which can grow on marginal soils and produce large amounts of biomass. Several conventional and advanced pretreatment methods have been developed to enhance the saccharification efficiency of plant biomass. Advanced pretreatment methods, such as microwave-assisted pretreatment methods are faster and use less energy compared to conventional pretreatment methods. In this study, we investigated the potential of Szarvasi biomass as a biorefinery feedstock. For this purpose, the lignocellulosic structure of Szarvasi biomass was investigated in detail. In addition, microwave-assisted pretreatments were applied to Szarvasi biomass using different reagents including weak acids and alkali. The produced pulp, hydrolysates, and extracted lignin were quantitatively characterized. In particular, the alkali pretreatment significantly enhanced the saccharification efficiency of the pulp 16-fold compared to untreated biomass of Szarvasi. The acid pretreatment directly converted 25% of the cellulose into glucose without the need of enzymatic digestion. In addition, based on lignin compositional and lignin linkage analysis a lignin chemical model structure present in Szarvasi biomass could be established.